(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
Behavioral therapy combined with a virtual reality exposure (VRE) component can be useful for the treatment of fears and phobias. This study aimed to: (a) describe and evaluate a behavioral therapy procedure amplified by VRE for the treatment of fear of height and (b) record sense of presence and cybersickness during exposure to assess the Virtua Therapy simulator. The procedure consisted of: an initial session; six therapy sessions, which included graduate exposure, prevention of escape-avoidance responses, and functional analyses of behaviors; two follow-up sessions. Sense of presence and cybersickness were recorded. The intervention decreased the participants’ levels of anxiety and the frequency of avoidance of situations involving heights in the virtual environment, and they reported decreases in day-to-day avoidance responses, demonstrating therapeutic effects. The simulator produced sense of presence. Cybersickness occurred primarily during the first session, indicating habituation effect. It was concluded that the Virtua Therapy simulator is an appropriate device for behavioral therapy.